PEMBUATAN SISTEM MONITORING KUALITAS AIR SECARA REAL TIME DAN APLIKASINYA DALAM PENGELOLAAN TAMBAK UDANG - Wiranto, Goib; Hermida, I Dewa Putu (LIPI Press, 2010)
In this paper it will be described the design and construction of a water quality monitoring system that can provide real time information about water quality parameters being measured. The main components of the system include a data logger with GSM based sms gateway, and two sensors for measuring DO and pH parameters. In addition to providing onsite measurement results, the system is also capable of giving the information through a mobile phone in case the DO or pH threshold value has been reached. On the contrary, the measured DO and pH values can also be known anytime via sms from mobile phone to the system. This system has been applied in the monitoring of water quality of shrimp ponds in Banyuwangi, East Java. Apart from providing realtime information, this system can also automatically turn on the turbines in the ponds if the DO value falls under the threshold. As such, the required oxygen supply needed by the shrimp can always be maintained.